Analisis Zona Defisiensi Nitrogen Tanah Berbasis Citra Landsat 8 dan Analisis Kimia di Kecamatan Sumbersari - Lathifatun Nisa' (Fakultas Pertanian, 2026)
Jember Regency is one of the fourth largest agricultural producers in Java. However, dry grain production in Jember Regency has decreased by 26.60 tons or 4.31%, and horticultural production in 2020 was only 5,668,005 kw or 23.8%. One of the main factors affecting agricultural productivity in Jember Regency is the large amount of land detected to have macro nutrient deficiencies, especially soil nitrogen in agriculture. Jember Regency, especially Sumbersari District, is classified as having low average nitrogen deficiency. This study uses a Landsat 8 image-based approach and chemical analysis to detect nitrogen deficiency in Sumbersari District. Sampling was conducted using purposive random sampling on agricultural land in Sumbersari District with a total of 33 samples. Landsat 8 images were analyzed using the NDVI, GNDVI, and SAVI vegetation indices. Soil samples were analyzed using the Kjeldahl method. The results showed a positive relationship between vegetation indices and chemical analysis. Simple linear regression produced the highest correlation in GNDVI with r = 0.23, 𝑅² = 0.05, and RMSE 0.09. Multiple linear regression of the three indices produced a higher correlation with r = 0.39, 𝑅² = 0.15, and RMSE = 0.09.
Keywords: N-Total; NDVI; GNDVI; SAVI